Abrasive processes for micro parts and structures. Issue 2 (2019) - Aurich, Jan C.; Kirsch, Benjamin; Setti, Dinesh; Axinte, Dragos; Beaucamp, Anthony; Butler-Smith, Paul; Yamaguchi, Hitomi
Abstract: The demand for miniaturized products and functionalized parts is increasing, and many such products are made of hard and brittle materials machined by abrasive processes. The first part of this keynote paper is dedicated to a discussion of micro parts and micro structures machined – at least in part – by abrasive processes, followed by a discussion of the associated abrasive processes. The strengths and limitations of these processes, among which include dicing, micro grinding, micro abrasive blasting, and vibration and magnet field assisted finishing are discussed. The paper concludes with a discussion of future trends in the field.